MnO2-coated graphitic petals for supercapacitor electrodes - Xiong, Guoping; Hembram, K.P.S.S.; Reifenberger, R.G.; Fisher, Timothy S. (Journal of power sources, 2013)
Hybrid manganese dioxide/graphitic petal structures grown on carbon nanotube substrates are shown to achieve high specific capacitance, energy density, power density, and long cycle life for flexible supercapacitor applications. Vertical nanoscale graphitic petals were prepared by microwave plasma chemical vapor deposition on commercial carbon nanotube substrates and subsequently coated with a thin layer of MnO2. The graphitic petal/carbon nanotube architecture without any binder provides an efficient scaffold for maximizing the electrochemical performance of MnO2. A specific capacitance (based on the mass of MnO2) of 580 F g−1 is obtained at a scan rate of 2 mV s−1 in 1 M Na2SO4 aqueous electrolyte. The energy density and power density at 50 A g−1 are 28 Wh kg−1 and 25 kW kg−1, respectively. In addition, the composite electrode shows excellent long-term cyclic stability (less than 10% decrease in specific capacitance after 1000 cycles) while maintaining a small internal resistance. Parallel density functional studies were performed to investigate the stability and electronic structure of the MnO2/graphene interface. Taken together, the work indicates the MnO2/graphitic petal/carbon nanotube composite is a promising electrode material for high-performance supercapacitors. [Display omitted] ► Buckypaper modified by graphitic petals to enhance area and chemical functionality. ► MnO2 coated on the carbon structure by a simple, solution-based method. ► Exceptional functional performance: 580 F g−1 (MnO2 mass basis), 44 Wh kg−1, 25 kW kg−1. ► Less than 10% degradation after 1000 CV cycles.